The Traceless Oldroyd viscoelastic model - Pires, Marília (2017)
In the traceless Oldroyd viscoelastic model, the viscoelastic extra stress tensor is decomposed into its traceless (deviatoric) and spherical parts, leading to a reformulation of the classical Oldroyd model. The equivalence of the two models is established comparing model predictions for simple test cases. The new model is validated using several 2D benchmark problems. The structure and behavior of the new model are discussed and the future use of the new model in envisioned, both on the theoretical and numerical perspectives.